2016
DOI: 10.1007/s13337-015-0294-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of evolutionary changes in hemagglutinin of influenza H1N1 virus: a computational analysis

Abstract: Influenza virus continues to evolve due to changes in the genome and the new strain of virus is more pathogenic then the previous strain. These changes may also help the virus to cross specie barrier and may also affect the binding pattern of virus.The main theme of the current study is the identification of changes in the hemagglutinin sequence of H1N1 virus from 1960 to 2011 and also how these changes affect the binding properties of virus. From 1960 to 2000 following important changes were observed: Ala198A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Additionally, as the authors concluded, classification and characterisation of all the sequences with the proposed methods, was difficult [5]- [7], thus a more advanced method is needed. Computational studies exist that tries to characterise and analyse the Influenza type A with promising results [8]. In the proposed method a computational, Artificial Neural Network (ANN) learning based approach is created to predict if a particular virus has the capability to infect humans, by only analysing the HA protein sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as the authors concluded, classification and characterisation of all the sequences with the proposed methods, was difficult [5]- [7], thus a more advanced method is needed. Computational studies exist that tries to characterise and analyse the Influenza type A with promising results [8]. In the proposed method a computational, Artificial Neural Network (ANN) learning based approach is created to predict if a particular virus has the capability to infect humans, by only analysing the HA protein sequence.…”
Section: Introductionmentioning
confidence: 99%